BOOKS RECENTLY PUBLISHED. (Notes, 2012)
The sources cited within this issue are presented including the books "Austronesian Soundscapes: Performing Arts in Oceania and Southeast Asia," edited by Birgit Abels, "Where the Action Was," by Mark Amans and "Lesbian Music of New Zealand," by Doreen Agassiz-Suddens.